Алгоритм прогнозування залишкового ресурсу деталей підіймального пристрою з поверхневими дефектами у вигляді тріщин - Носов, Юрій (КІНПАТРІ ЛТД, 2013)
In this article are displayed the algorithm for calculation the durability of building lifting device parts which have surface defects in the form of the cracks. During calculations take into account the influence of nonstationary loads of lifting system elements that arise during starting, braking or mode changing of the drive.
The algorithm of residual resourse predictin of lifting device parts with surface defects in the form of the cracks